Modelo para avaliação da vida útil econômica de máquinas e equipamentos utilizando a programação dinâmica e o método de Monte Carlo - Plizzari, Ricardo (My University, 2017)
The replacement study of capital goods provides to the company an overview about the useful life of its assets and provides planning for effecting, within an optimal time, the exchange of the present good by a substitute that may offer advantages with respect to Costs of operation and maintenance, being possible to obtain the maximization of revenues. This dissertation proposes a model for evaluation of economic useful life of machines and equipment making use of dynamic programming (PD) with the generation of random numbers by the Monte Carlo method (MMC). The model includes variables definition that will be used, the application of the Monte Carlo method to the variables, calculation of the present values, dynamic programming calculations with the objective of defining the maximum revenues, the programming development using MatLab software and validation of model. The simulations were performed using the discount rates based on the IPCA, CDI, IGP-M, Selic and Selic targets. The use of Monte Carlo method allowed the generation of a series of policies for each simulation, being analysed statistically as a way to verify the one that would best represent the replacement policy and consequently defined the economic useful life of the good. The model was applied to a vertical milling centre and showed flexibility in the information of the input data when using the programming in the software MatLab. It was observed that in addition to generating a range of possibilities the PD+MMC model can assist the decision maker regarding the strategy to be used in the replacement of machine. The PD + MMC calculations, for a 15-year planning horizon, using the five discount rates, provided replacement policies with economic life estimated 3-year economic life for the CDI, Selic and Selic and Useful life over 15 years for the IPCA and IGP-M rates. The PD+MMC calculations for a planning horizon of 15 years, using the five discount rates, provided replacement policies with three years useful life estimate for CDI, Selic and target Selic rates and for the IPCA and plus than fifteen years useful life for IPCA and IGP-M rates. By means of the statistical analyzes it was possible to define that the substitution policy that presented the highest reliability was the one that used the IPCA / IBGE, which generated the highest revenue and the longest useful life of the machine, over 16 years, presenting a significance of 77, 56% for policy frequency.
O estudo da substituição de bens de capital proporciona a empresa uma visão sobre a vida útil dos seus bens e oportuniza o planejamento para efetuar, dentro de um tempo ótimo, a troca do bem atual por um substituto que possa oferecer vantagens no que diz respeito a custos de operação e manutenção, sendo possível obter com isso a maximização das receitas. Esta dissertação propõe um modelo para a avaliação da vida útil econômica de máquinas e equipamentos fazendo uso da programação dinâmica (PD) com a geração de números aleatórios por meio do método de Monte Carlo (MMC). O modelo contempla a definição das variáveis que serão utilizadas, a aplicação do método de Monte Carlo às variáveis, o cálculo dos valores presentes, os cálculos da programação dinâmica com o objetivo de definir a máxima receita, o desenvolvimento da programação com o uso do software MatLab e a validação do modelo. As simulações foram realizadas utilizando as taxas de desconto baseadas no IPCA, CDI, IGP-M, Selic e meta Selic. A utilização do método de Monte Carlo possibilitou a geração de uma série de políticas para cada simulação, sendo estas analisadas estatisticamente como forma de verificar aquela que melhor representaria a política de substituição e consequentemente definisse a vida útil econômica do bem. O modelo foi aplicado a um centro de usinagem vertical e demonstrou flexibilidade na informação dos dados de entrada ao se utilizar a programação no software MatLab. Observou-se que além de gerar uma gama de possibilidades o modelo PD+MMC pode auxiliar o tomador de decisão quanto a estratégia a ser utilizada na substituição da máquina. Os cálculos efetuados por meio do modelo PD+MMC, para um horizonte de planejamento de 15 anos, utilizando as cinco taxas de desconto, forneceram políticas de substituição com estimativas de vida útil econômica de 3 anos para as taxas CDI, Selic e meta Selic e vida útil superior a 15 anos para as taxas IPCA e IGP-M. Por meio das análises estatísticas foi possível definir que a política de substituição que apresentou maior confiabilidade foi a que utilizou o IPCA/IBGE, a qual gerou a maior receita e a maior vida útil da máquina, superior a 16 anos, apresentando significância de 77,56% para a frequência de políticas.
Keywords: Programação dinâmica; Monte Carlo, Método de; Máquinas; MATLAB; Dynamic programming; Monte Carlo method; Machinery